PAIN AND INFLAMMATION. PART 2. THE ANALGESIC POTENTIAL OF ANTI-INFLAMMATORY DRUGS - A. E. Karateev; D. E. Karateev; O. S. Davydov (Научно-практическая ревматология)
An inflammatory response and the development of pain are interdependent processes. Inflammation accompanied by the overproduction of proinflammatory cytokines and mediators not only causes pain, but is also the main cause of its chronicity. Therefore, the use of anti-inflammatory drugs should be considered to be the mainstay of analgesic therapy. Part 2 of the review discusses the analgesic potential of various pharmacological groups that have an anti-inflammatory effect: nonsteroidal anti-inflammatory drugs, glucocorticoids, biological agents, methotrexate, slow-acting antiinflammatory drugs (chondroprotectors), as well as a number of promising and experimental agents, such as nerve growth factor inhibitors. It provides data from major clinical trials that have evaluated the analgesic effect of these drugs in various diseases and pathological conditions.